Betrayal : how Black intellectuals have abandoned the ideals of the civil rights era - Baker, Houston A., Jr., 1943- (Columbia University Press, 2008)
Houston A. Baker Jr. condemns those black intellectuals who, he believes, have turned their backs on the tradition of racial activism in America. These individuals choose personal gain over the interests of the black majority, whether they are espousing neoconservative positions that distort the contours of contemporary social and political dynamics or abandoning race as an important issue in the study of American literature and culture. Most important, they do a disservice to the legacy of W.E.B. Du Bois, Martin Luther King Jr., and others who have fought for black rights. In the literature, speeches, and academic and public behavior of some black intellectuals in the past quarter century, Baker identifies a "hungry generation" eager for power, respect, and money. Baker critiques his own impoverished childhood in the "Little Africa" section of Louisville, Kentucky, to understand the shaping of this new public figure. He also revisits classical sites of African American literary and historical criticism and critique. Baker devotes chapters to the writing and thought of such black academic superstars as Cornel West, Michael Eric Dyson, and Henry Louis Gates Jr.; Hoover Institution senior fellow Shelby Steele; Yale law professor Stephen Carter; and Manhattan Institute fellow John McWhorter. His provocative investigation into their disingenuous posturing exposes what Baker deems a tragic betrayal of King's legacy.